2019
DOI: 10.1101/558171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ClassiPhages 2.0: Sequence-based classification of phages using Artificial Neural Networks

Abstract: 11Background/ Motivation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Over the last few years, whole genome and proteome analysis has been applied as a basis for new taxonomic insights that may lead to a phylogeny‐based classification of phages (Chibani et al., 2019; Adriaenssens et al., 2020) and, potentially, of all viruses (Moreno‐Gallego and Reyes, 2021). However, although these new insights may open new perspectives for the future classification of phages, the QPS WG concluded that the actual taxonomic situation is still unsettled and not generally accepted.…”
Section: Assessmentmentioning
confidence: 99%
“…Over the last few years, whole genome and proteome analysis has been applied as a basis for new taxonomic insights that may lead to a phylogeny‐based classification of phages (Chibani et al., 2019; Adriaenssens et al., 2020) and, potentially, of all viruses (Moreno‐Gallego and Reyes, 2021). However, although these new insights may open new perspectives for the future classification of phages, the QPS WG concluded that the actual taxonomic situation is still unsettled and not generally accepted.…”
Section: Assessmentmentioning
confidence: 99%
“…The program and profile HMMs for the four phage families listed above is available for download (27). This work was extended to create ClassiPhage 2.0, an updated method that uses profile HMMs derived from phage sequences to train an Artificial Neural Network (ANN) to classify the phages into one of 12 different families (28). The generated models showed very high specificity for all families, but the observed sensitivity was very low, with only 3 out of the 12 families showing values above 50% and six families presenting sensitivity below 20%.…”
Section: Databases Of Viral Profile Hmmsmentioning
confidence: 99%
“…Our goal was also to create a bioinformatic tool for predicting the host from the whole genome sequence, but we chose the machine-learning-algorithm approach. The use of machine learning algorithms has proved to be suitable for phage biology, as evidenced by their use in the search for phage virions [ 37 ], and improved phage genome annotation [ 38 ] as well as phage classification [ 39 , 40 ]. Our pipeline, PHERI, re-annotates phage genomes, and uses TRIBE-MCL for rapid and accurate clustering of annotated protein sequences [ 41 , 42 ] and a binary decision tree classifier to predict the phage host.…”
Section: Introductionmentioning
confidence: 99%